2013
DOI: 10.1002/eat.22235
|View full text |Cite
|
Sign up to set email alerts
|

Set shifting in children and adolescents with anorexia nervosa: An exploratory systematic review and meta‐analysis

Abstract: The inefficiencies in set shifting that are apparent in the adult AN literature do not appear to be as pronounced in children. This may suggest that set shifting difficulties in adult AN are the result of starvation or indicative of longer duration of illness. Larger studies are needed to confirm these impressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 25 publications
9
113
0
4
Order By: Relevance
“…However, it is clear from both the present review and an earlier review of set-shifting abilities in children [10], that a lack of data in this area currently limits us from drawing firm conclusions about the profile of children and adolescents with AN. Further research is therefore needed to firstly confirm the neurocognitive profile of young group with AN, and then secondly to determine whether remedial treatments are required in this population.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, it is clear from both the present review and an earlier review of set-shifting abilities in children [10], that a lack of data in this area currently limits us from drawing firm conclusions about the profile of children and adolescents with AN. Further research is therefore needed to firstly confirm the neurocognitive profile of young group with AN, and then secondly to determine whether remedial treatments are required in this population.…”
Section: Discussionmentioning
confidence: 57%
“…A recent systematic review and meta-analysis aimed to clarify set shifting abilities of children and adolescents with AN [10]. Overall this review found no significant differences between children with and without AN.…”
Section: Introductionmentioning
confidence: 79%
“…The findings of this study suggesting that there are in fact no differences in the perception of sweetness or fat intensity between people with AN and HC indicates that the documented aversion to this stimuli in individuals with AN reflects subjective perception, rather than objective taste alterations. Instead, sweetness and fat avoidance in AN may instead be driven by the cognitive resistance and inflexibility documented in this population (Lang, Stahl, Espie, Treasure, & Tchanturia, 2014; Tchanturia et al, 2012; Westwood, Stahl, Mandy, & Tchanturia, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Limits included English-language, peer-reviewed articles. Reference lists of eligible papers were also screened, as were existing systematic reviews related of set-shifting in either ASD or AN (Roberts et al 2007;Lang et al 2014;Tchanturia, 2015;Landry & Al-Taie, 2016).…”
Section: Information Sources and Searchmentioning
confidence: 99%
“…A systematic review of set-shifting ability, comparing adults with AN with HCs identified five papers employing the Wisconsin Card Sorting Test (WCST) (Heaton et al 1993), a widely used measure of set-shifting, with a meta-analysis reporting a significant small effect size (d = 0.36; Roberts et al 2007). A further meta-analysis of studies in children and adolescents with AN (Lang et al 2014), however, found a non-significant pooled effect size (d = 0.20). A more recent study comparing children and adolescents with AN with HCs using a larger sample size (AN = 41, HC = 43) found that young people with AN made significantly more perseverative errors than HCs (d = 0.49; Lang et al 2015a), suggesting that this cognitive profile is present early on in the disorder before the effects of starvation become prominent.…”
Section: Introductionmentioning
confidence: 99%